(untitled) (Journal of Environmental Science and Natural Resources, 2016)
The experiment was conducted at Horticulture Research Centre, Gazipur, Bangladesh, to study the effects of N, P, K, and S on growth, yield and nutrient content of strawberry following Randomized Complete Block Design (RCBD) method. There were 4 levels of different nutrients and there was a positive impact of each fertilizer combinations on yield, yield parameters and nutrient contents of BARI Strawberry except control treatment. The highest values of plant height (25.60 cm); number of leaves (21.66), flowers (125.33), fruits (12.35),destroyed fruits (11), fruit weight (215.10 g) plant-1 and fruit length (4.16 cm), fruit diameter (3.41cm), individual fruit weight (17.85 g) and fruit yield (11.50 t ha-1) were found in treatment of 115,40,110 and 25 kg ha-1NPKS, respectively. Among the fertilizers, the single effect of N (115 kg ha-1), P (40 kg ha-1), K (110 kg ha-1) and S (25 kg ha-1) gave maximum growth and yield of strawberry. The highest concentration of N, P, K and S were found in shoot and fruit of strawberry when N, P, K and S fertilizers were used 140,60,135 and 35 kg ha-1, respectively. J. Environ. Sci. & Natural Resources, 9(1): 99-108 2016